2015
DOI: 10.1113/jphysiol.2014.282319
|View full text |Cite
|
Sign up to set email alerts
|

Na+/Ca2+ exchange and Na+/K+‐ATPase in the heart

Abstract: This paper is the third in a series of reviews published in this issue resulting from the University of California Davis Cardiovascular Symposium 2014: Systems approach to understanding cardiac excitation–contraction coupling and arrhythmias: Na+ channel and Na+ transport. The goal of the symposium was to bring together experts in the field to discuss points of consensus and controversy on the topic of sodium in the heart. The present review focuses on cardiac Na+/Ca2+ exchange (NCX) and Na+/K+-ATPase (NKA). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
157
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(168 citation statements)
references
References 252 publications
(531 reference statements)
7
157
0
1
Order By: Relevance
“…The increased intracellular Ca 2+ will also activate NCX expressed in ASM [41,42]. We found that when NCX was inhibited by replacing Na + with Li + , the TEA-induced oscillatory contractions were transiently enhanced and then disappeared (Fig.…”
Section: Figmentioning
confidence: 81%
See 1 more Smart Citation
“…The increased intracellular Ca 2+ will also activate NCX expressed in ASM [41,42]. We found that when NCX was inhibited by replacing Na + with Li + , the TEA-induced oscillatory contractions were transiently enhanced and then disappeared (Fig.…”
Section: Figmentioning
confidence: 81%
“…In addition, NCX will induce cytosolic Na + increases, which will then activate Na + /K + -ATPase [42,43]. Following the inhibition of this enzyme by ouabain, a larger contraction was observed and the oscillatory contractions then vanished (Fig.…”
Section: Figmentioning
confidence: 99%
“…As a result of this mechanism, the junctional cleft is primed with Ca 2+ , facilitating EC-coupling. During diastole, cytosolic Ca 2+ increases from RyR2 activation promote Ca 2+ extrusion through NCX activity [37]. …”
Section: Ec Coupling and Hfmentioning
confidence: 99%
“…It has been proposed that NCX activity is up-regulated in failing heart [38], but divergent evidence also exists [37]. SR Ca 2+ leak increases cytosolic Ca 2+ and forward mode-dependent Ca 2+ extrusion, exacerbating declines in SR Ca 2+ and promoting Na + entry [13].…”
Section: Ec Coupling and Hfmentioning
confidence: 99%
“…The eukaryotic exchanger is composed of 10 transmembrane domains (TM) (11,12), with a large cytosolic loop between TM5 and TM6. Deletion of the cytosolic loop has revealed that it does not play a direct role in ion translocation, but rather it mediates regulation of the exchanger by associating with various cytosolic factors (13)(14)(15)(16).…”
mentioning
confidence: 99%